Crossover clinical trial of different methods of removing a denture adhesive and the influence on the oral microbiota - Nunes, Élen Massaro [UNESP]; Policastro, Vivian Barnabé [UNESP]; Scavassin, Priscila Mattos [UNESP]; Leite, Andressa Rosa Perin [UNESP]; Mendoza Marin, Danny Omar [UNESP]; Giro, Gabriela [UNESP]; De Oliveira Júnior, Norberto Martins [UNESP]; Compagnoni, Marco Antonio [UNESP]; Pero, Ana Carolina [UNESP] (Elsevier, 2016)
Statement of problem The difficulty of removing denture adhesive is a common problem reported by users of these products. Purpose The purpose of this clinical study was to investigate the effectiveness of different cleaning protocols for removing a denture adhesive (DA) and the influence on the oral microbiota. Material and methods Twenty participants wearing well-fitting complete dentures were instructed to use a denture adhesive 3 times a day during a 4-week trial, divided into 4 stages: (A) control - 3 daily denture brushings using water at ambient temperature, (B) - 3 daily denture brushings using water at ambient temperature plus coconut soap, (C) - 3 daily denture brushings using water at ambient temperature plus dentifrice; (D) - 3 daily denture brushings using water at ambient temperature combined with immersion in sodium perborate solution for 5 minutes before nocturnal sleep. After each 1-week stage, saliva specimens were collected. A dye was used to display and quantify the remaining DA on the internal surface of the maxillary dentures as a percentage. For microbiological analysis, the saliva was diluted and plated onto Petri dishes containing a nonselective culture medium and Candida spp culture media. After the incubation period, Candida species were identified and the number of colony forming units (CFU/mL) was calculated. Results A significant difference was found among the 4 cleaning methods for the quantification of remaining DA (Friedman, P=.036). Brushing the dentures with coconut soap, dentifrice, or water combined with immersion in sodium perborate solution was more effective in removing DA than brushing with only water. The cleaning methods did not influence the quantification of microorganisms in general or Candida albicans and other Candida species in particular. Conclusions Brushing the dentures with coconut soap, dentifrice, or water combined with immersion in sodium perborate solution was more effective for removing cream-type denture adhesive than brushing with only water.